2004
DOI: 10.1074/jbc.m312119200
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IKKβ-IKKγ Subcomplexes in Monocytic Cells and Characterization of Associated Signaling

Abstract: The I B kinase (IKK) complex is one major step in the regulation of the NF-B/Rel system that is involved in inflammatory and immune responses as well as in proliferation and apoptosis. At present it is not clear whether besides the "classical" IKK␣-IKK␤-IKK␥ configuration additional complexes exist in vivo that solely contain IKK␤ and IKK␥ (without IKK␣). In the current study we were able to demonstrate in monocytic cells that endogenous complexes, which only include IKK␤ as the kinase-active molecule do indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…In any event, the rapid fall in IKK␣ levels observed upon neutrophil stimulation indicates that to a great extent, the activated and functional IKK complex of neutrophils must mainly comprise IKK␤ and IKK␥. Such a scenario is consistent with the recent demonstration that endogenous IKK␤-IKK␥ subcomplexes exist in the cytosplasm of human monocytic THP-1 cells, and display increased IKK activity following cell stimulation with TNF (59). Similarly, immunodepletion studies showed the presence of IKK␤-IKK␥ complexes activated by anti-CD3/CD28 in primary human T cells (60).…”
Section: Discussionsupporting
confidence: 75%
“…In any event, the rapid fall in IKK␣ levels observed upon neutrophil stimulation indicates that to a great extent, the activated and functional IKK complex of neutrophils must mainly comprise IKK␤ and IKK␥. Such a scenario is consistent with the recent demonstration that endogenous IKK␤-IKK␥ subcomplexes exist in the cytosplasm of human monocytic THP-1 cells, and display increased IKK activity following cell stimulation with TNF (59). Similarly, immunodepletion studies showed the presence of IKK␤-IKK␥ complexes activated by anti-CD3/CD28 in primary human T cells (60).…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, the differential effect of the Ser 68 phosphorylation on the IKK␣ or IKK␤ interaction could have variable effects on IKK complexes depending on whether they contain IKK␣-IKK␤ heterodimers or homodimers of IKK␣ or IKK␤. Indeed, differences in the activity and regulation of IKK␣-IKK␤ heterodimers and IKK␤-homodimers have been observed (15). Furthermore, the recently described IKK␣-NEMO and IKK␤-NEMO heterodimers suggest the existence of different subpools of IKK complexes with a different composition regarding IKK␣-homodimers, IKK␤-homodimers, and/or IKK␣-IKK␤-heterodimers (22).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Recently, it was shown that the main function of IKKa binding to IKKb and IKKg is to increase the activity of IKK complex and to accelerate downstream signaling pathways such as proteolysis of IjBa. 35 Earlier investigations in our laboratory have shown that, although prostate cancer cells respond to TRAIL treatment, some cell lines, such as LNCaP, are resistant. Therefore, we have been exploring combination therapies to sensitize these cells to TRAIL and to understand the mechanism by which these cells are sensitized.…”
mentioning
confidence: 99%